Transposition of tense forms of the Russian verb as a means of grammatical figurativeness - Popova E.I, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the nature of the transposition of tense forms as a phenomenon of grammatical figurativeness. One of the ways of grammatical metaphorization is the contrast between the grammatical meaning of the form and the context. The use of temporary forms in an environment unusual for them is characterized, i.e. as transposition. The analysis of cases of the figurative use of temporary forms makes it possible to figuratively and expressively present the implementation of the process in time, to clarify its modal characteristics, semantic and expressive shades